Cognitive and affective benefits of combination therapy with galantamine plus cognitive rehabilitation for Alzheimer's disease. Issue 4 (8th May 2015) - Tokuchi, Ryo; Hishikawa, Nozomi; Matsuzono, Kosuke; Takao, Yoshiki; Wakutani, Yosuke; Sato, Kota; Kono, Syoichiro; Ohta, Yasuyuki; Deguchi, Kentaro; Yamashita, Toru; Abe, Koji
Abstract : Aim: The aim of the present study was to compare the effects of a galantamine only therapy and a combination therapy with galantamine plus ambulatory cognitive rehabilitation for Alzheimer's disease patients. Methods: For this retrospective cohort study, we enrolled 86 patients with Alzheimer's disease, dividing them into two groups – a galantamine only group (group G, n = 45) and a combination with galantamine plus ambulatory rehabilitation group (group G + R, n = 41). The present cognitive rehabilitation included a set of physical therapy, occupational therapy and speech therapy for 1–2 h once or twice a week. We compared the Mini‐Mental State Examination and Frontal Assessment Battery for cognitive assessment, and Geriatric Depression Scale, Apathy Scale, and Abe's Behavioral and Psychological Symptoms of Dementia score for affective assessment in two groups over 6 months. Results: The baseline Mini‐Mental State Examination score was 20.2 and 18.7 in groups G and G + R, respectively. Other baseline data (Frontal Assessment Battery, Geriatric Depression Scale, Apathy Scale, and Abe's Behavioral and Psychological Symptoms of Dementia) were not different between the two groups. Although group G kept all the scores stable until 6 months of the treatment, the Apathy Scale score showed a significant improvement in group G + R as early as 3 months, followed by the Mini‐Mental State Examination and Frontal Assessment Battery improvements at 6 months (* P = 0.04 and * P = 0.02, respectively). The Geriatric Depression Scale and Abe's Behavioral and Psychological Symptoms of Dementia did not show any changes. Conclusion: The combination therapy of galantamine plus ambulatory cognitive rehabilitation showed a superior benefit both on cognitive and affective functions than galantamine only therapy in Alzheimer's disease patients.Geriatr Gerontol Int 2016; 16: 440‐445.